2009
DOI: 10.1007/s10562-009-9908-z
|View full text |Cite
|
Sign up to set email alerts
|

Epoxidation of Cyclohexene with Air over the Composite Catalysts of Mn-mont Coordinated with Ligands

Abstract: The catalytic activity of the composite catalysts of Mn-mont (where mont represents montmorillonite) coordinated with ligands for the epoxidation of cyclohexene by air under Mukaiyama conditions was studied. The composite catalysts were characterized by atomic absorption spectroscopic analysis, elemental analysis, fourier transform infrared spectra, diffuse reflectance ultraviolet visible spectra, X-ray photoelectron spectroscopy, powder-X-ray-diffraction, and scanning electron microscopy measurements. The eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…6). 70,71 In the absence of catalyst, cyclohexene gave only 12% conversion; no epoxide was found. Through GC analysis, 1,2cyclohexanediol was not detected in the reaction mixture.…”
Section: Catalytic Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…6). 70,71 In the absence of catalyst, cyclohexene gave only 12% conversion; no epoxide was found. Through GC analysis, 1,2cyclohexanediol was not detected in the reaction mixture.…”
Section: Catalytic Activitymentioning
confidence: 99%
“…Through GC analysis, 1,2cyclohexanediol was not detected in the reaction mixture. 70,71 In the absence of catalyst, cyclohexene gave only 12% conversion; no epoxide was found. 72 Since the CeO 2 catalytic test gave a result similar to the one without catalyst, it can be concluded that the support was not active.…”
Section: Catalytic Activitymentioning
confidence: 99%
“…Jiang and Ma 3 reported that the Co(II)-Schiff base complex which was synthesized from salicylaldehyde was found to be an efficient catalyst for the oxidation of cyclohexene (94% conversion and 82% selectivity of epoxycyclohexane). Unfortunately, the selectivity of epoxycyclohexane in these methods was still lower than industrial standards and some methods 11,12 consumed a large amount of isobutyraldehyde.…”
Section: Introductionmentioning
confidence: 99%